Pengaruh Social Media Influencer Credibility dan E-WOM Terhadap Purchase Intention Skincare Produk Lokal Di Jabodetabek Melalui Brand Trust Sebagai Variabel Mediasi - Siti Khairul Aini; Setyo Ferry Wibowo; Nofriska Krissanya (Teewan Journal Solutions, 2025)
This study investigates the impact of social media influencer credibility and e-WOM on the purchase intention of local skincare products in Jabodetabek, with brand trust as a mediating variable. The study highlights the significant role of social media influencer credibility and e-WOM in shaping consumer perceptions and behaviors in the skincare industry. By examining the interaction between these factors, this research provides valuable insights into the dynamics of brand trust and purchase intention. Using a quantitative approach, the study involved 300 respondents who are consumers of local skincare products. Data were analyzed using AMOS version 24 software and the Structural Equation Modeling (SEM) method. The findings indicate that social media influencer credibility and e-WOM significantly influence purchase intention, with brand trust serving as an important mediator in this relationship. However, social media influencer credibility does not directly affect purchase intention. This study contributes to the understanding of marketing strategies in the skincare industry, emphasizing the importance of building trust through credible influencers and positive e-WOM to enhance consumer engagement and sales.